2022
DOI: 10.1097/ccm.0000000000005493
|View full text |Cite
|
Sign up to set email alerts
|

CytoSorb Rescue for COVID-19 Patients With Vasoplegic Shock and Multiple Organ Failure: A Prospective, Open-Label, Randomized Controlled Pilot Study*

Abstract: OBJECTIVES: To investigate the effect of extracorporeal cytokine reduction by CytoSorb (CytoSorbents, Monmouth Junction, NJ) on COVID-19–associated vasoplegic shock. DESIGN: Prospective, randomized controlled pilot study. SETTING: Eight ICUs at three sites of the tertiary-care university hospital Charité—Universitätsmedizin Berlin. PATIENTS: COVID-19 patients with vasoplegic shock requiring norepinephrine greater than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
68
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 35 publications
(63 reference statements)
4
68
0
2
Order By: Relevance
“…Indeed, systemic concentrations of pro-inflammatory cytokines in patients with severe COVID-19 are not as high as has been reported in patients with other causes of acute respiratory distress syndrome. The study results by Stockmann et al ( 1 ) are in line with the results of another randomized controlled study in patients with septic shock and multiple organ failure in which CytoSorb removed IL-6, but the removal had no effect on systemic IL-6-levels ( 10 ). So calming the storm, as one of the miracles of Jesus in a fierce storm sailing the Sea of Galilee, seems to be a challenging endeavor.…”
supporting
confidence: 71%
See 3 more Smart Citations
“…Indeed, systemic concentrations of pro-inflammatory cytokines in patients with severe COVID-19 are not as high as has been reported in patients with other causes of acute respiratory distress syndrome. The study results by Stockmann et al ( 1 ) are in line with the results of another randomized controlled study in patients with septic shock and multiple organ failure in which CytoSorb removed IL-6, but the removal had no effect on systemic IL-6-levels ( 10 ). So calming the storm, as one of the miracles of Jesus in a fierce storm sailing the Sea of Galilee, seems to be a challenging endeavor.…”
supporting
confidence: 71%
“…“However beautiful the strategy, you should occasionally look at the results.” is a famous saying by Sir Winston Churchill. In this issue of Critical Care Medicine , Stockmann et al ( 1 ) did exactly that by looking at the result of a well-performed randomized controlled trial in which they investigated an intriguing strategy, namely the use of a cytokine adsorber, in patients with COVID-19 in vasoplegic shock ( 2 ). In contrast to a growing popular belief, they neither showed any difference in the need for catecholamines nor in the mortality nor in other secondary outcomes, including interleukin (IL)-6 and C-reactive protein (CRP) levels.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Stockmann et al [ 55 ] noted that the removal of cytokines using CytoSorb in critically ill COVID-19 patients with suspected generalized inflammation and shock can be an excellent way of stabilizing hemodynamics and improving the clinical outcome. However, in a large open-label randomized controlled trial involving patients with severe COVID-19, they showed that the use of CytoSorb did not prevent the development of Vasoplegic shock; moreover, mortality level in the CytoSorb and control groups was almost the same at 78% and 73%, respectively [ 56 ].…”
Section: Hemoadsorptionmentioning
confidence: 99%